2019
DOI: 10.1111/cdev.13209
|View full text |Cite
|
Sign up to set email alerts
|

Essentialization of Social Categories Across Development in Two Cultures

Abstract: Children display an “essentialist” bias in their everyday thinking about social categories. However, the degree and form of this bias varies with age and with the nature of the categories, as well as across cultures. This project investigated the development of the essentialist bias across five social categories (i.e., gender, nationality, religious affiliation, socioeconomic status (rich/poor), and sports‐team supporter) in two countries. Children between 5 and 10 years of age in Turkey (Study 1, N = 74) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(104 citation statements)
references
References 42 publications
4
97
1
2
Order By: Relevance
“…The myth of interest in this section is the idea that children are predisposed to think of differences between people through the same essentialist lens through which they understand animal species-that they inevitably think of differences between boys and girls, or White people and Black people, for example, in the same way as they think about the difference between tigers and sheep. Researchers from various disciplines have proposed that some social differences appear to the human mind to pattern like differences in animal species, either because they appear to be inherited from parents or to correlate with physical feature differences in a similar manner as species categories do (Davoodi, Soley, Harris, & Blake, 2019;Gil-White, 2001), or because they are labeled with the same type of noun labels that are frequently used to refer to basiclevel animal species (e.g., referring to "girls" and "boys", in the same way as one might refer to "tigers" and "sheep"; Hirschfeld, 1996;Waxman, 1990). From this perspective, when people confront such differences, they cannot help but think of them as reflecting the same types of essential differences that they believe structure the biological world.…”
Section: Myth 3: People Inevitably Think Of Differences Between Peoplmentioning
confidence: 99%
“…The myth of interest in this section is the idea that children are predisposed to think of differences between people through the same essentialist lens through which they understand animal species-that they inevitably think of differences between boys and girls, or White people and Black people, for example, in the same way as they think about the difference between tigers and sheep. Researchers from various disciplines have proposed that some social differences appear to the human mind to pattern like differences in animal species, either because they appear to be inherited from parents or to correlate with physical feature differences in a similar manner as species categories do (Davoodi, Soley, Harris, & Blake, 2019;Gil-White, 2001), or because they are labeled with the same type of noun labels that are frequently used to refer to basiclevel animal species (e.g., referring to "girls" and "boys", in the same way as one might refer to "tigers" and "sheep"; Hirschfeld, 1996;Waxman, 1990). From this perspective, when people confront such differences, they cannot help but think of them as reflecting the same types of essential differences that they believe structure the biological world.…”
Section: Myth 3: People Inevitably Think Of Differences Between Peoplmentioning
confidence: 99%
“…In line with this, past research showed that children growing up in more homogenous environments exhibit higher degrees of essentialist thinking about a given social category (Pauker et al, 2016;Smyth, Feeney, Eidson, & Coley, 2017) and that verbal cues, such as the use of generic language, are shown to influence the development of essentialist beliefs in children (Rhodes et al, 2012;Segall, Birnbaum, Deeb, & Diesendruck, 2015). Importantly, the role of each of these variables over and above the others may not be always easily discernible, given that they might tend to co-vary (Davoodi et al, 2020b). For instance, parents might use explicit labelling and generics more frequently when talking about social categories that have biological underpinnings (e.g., girls like dolls).…”
Section: Psikoloji çAlışmaları -Studies In Psychologymentioning
confidence: 95%
“…To this date, only one study examined children's essentialist views of human social categories in Turkey. This study examined essentialist beliefs about gender, nationality, religion, socio-economic status, and sports teams among 5-to-10-year-old children and adults in Turkey and in the U.S. (Davoodi et al, 2020b). The results of the study showed notable similarities across the two cultures.…”
Section: Psikoloji çAlışmaları -Studies In Psychologymentioning
confidence: 99%
“…In support of this possibility, studies show that the more that adults essentialize a social group, the more they support the enforcement of prescriptive rules about group membership (Meyer & Gelman, 2016;Roberts et al, 2017), and that adults with higher essentialist biases are less supportive of ethnic nationalist diversity and immigration (Rad & Ginges, 2018), more supportive of assimilation (Bastian & Haslam, 2008) and less willing to help asylum seekers (Pehrson, Brown, & Zagefka, 2009). Recent evidence suggests that children aged 5 to 9 in both the U.S. and Turkey do essentialize nationality (Davoodi, Soley, Harris, & Blake, 2019). Younger children may be particularly likely to essentialize members of their own nation and other nations, with a reduction in this tendency from ages 5 to 11 (Barrett, 2000).…”
Section: Author Manuscript Development Of Religious Nationalism In Indiamentioning
confidence: 99%